Updates on Clinical and Genetic Heterogeneity of ASPM in 12 Autosomal Recessive Primary Microcephaly Families in Pakistani Population - Khan, Niaz Muhammad; Hussain, Basharat; Zheng, Chenqing; Khan, Ayaz; Masoud, Muhammad Shareef; Gu, Qingquan; Qiu, Linhui; Malik, Naveed Altaf; Qasim, Muhammad; Tariq, Muhammad; Chang, Junlei (Frontiers in Pediatrics, 2021)
Microcephaly (MCPH) is a genetically heterogeneous disorder characterized by non-progressive intellectual disability, small head circumference and brain size compared to the age and sex matched population. MCPH manifests as an isolated condition or part of another clinical syndrome, so far, 25 genes have been linked with MCPH. Many of these genes are reported in Pakistani population, but due to high rate of consanguinity, a significant proportion of MCPH cohort is yet to be explored. MCPH5 is the most frequently reported type, accounting for up to 68.75% alone in genetically constrained population like Pakistan. In the current study, Whole Exome Sequencing (WES) was performed on probands from 10 families sampled from South Waziristan and 2 families from rural areas of the Pakistani Punjab. Candidate variants were validated through Sanger sequencing in all available family members. Variant filtering and In silco analysis identified three known mutations in ASPM, a MCPH5 associated gene. The founder mutation p.Trp1326* segregate in 10 families, which further confirmed the evidence that it is the most prominent mutation in Pashtun ethnicity living in Pakistan and Afghanistan. Furthermore, previously known mutations p.Arg3244* and p.Arg1019* were inherited in two families with Punjab ethnic profile. Collectively, this study added 12 more families to the mutational paradigm of ASPM and expanded the Pakistani MCPH cohort.